A chemotactic signaling surface on CheY defined by suppressors of flagellar switch mutations. - Roman, S J (1992)
CheY is the response regulator protein that interacts with the flagellar switch apparatus to modulate flagellar rotation during chemotactic signaling. CheY can be phosphorylated and dephosphorylated in vitro, and evidence indicates that CheY-P is the activated form that induces clockwise flagellar rotation, resulting in a tumble in the cell's swimming pattern. The flagellar switch apparatus is a complex macromolecular structure composed of at least three gene products, FliG, FliM, and FliN. Genetic analysis of Escherichia coli has identified fliG and fliM as genes in which mutations occur that allele specifically suppress cheY mutations, indicating interactions among these gene products. We have generated a class of cheY mutations selected for dominant suppression of fliG mutations. Interestingly, these cheY mutations dominantly suppressed both fliG and fliM mutations; this is consistent with the idea that the CheY protein interacts with both switch gene products during signaling. Biochemical characterization of wild-type and suppressor CheY proteins did not reveal altered phosphorylation properties or evidence for phosphorylation-dependent CheY multimerization. These data indicate that suppressor CheY proteins are specifically altered in the ability to transduce chemotactic signals to the switch at some point subsequent to phosphorylation. Physical mapping of suppressor amino acid substitutions on the crystal structure of CheY revealed a high degree of spatial clustering, suggesting that this region of CheY is a signaling surface that transduces chemotactic signals to the switch.